Struktur Pembentukan Kosakata Kanji Majemuk Bahasa Jepang (Nihongo no Kanji Jukugo no Gokeisei) - Oni Kurnia Sari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
This study is focus to analyze the Kanji compound in Japanese language. Thepurpose of this study is to understand and discover comprehensively of the modificationstructure of kanji compound in Japanese language. So that there will be no errors incomprehension them particularly for students.The methods applied in this study is descriptive where the primary data gatheredfrom Asahi Newspaper.Keywords: Kanji, Japanese language